Financial Crisis, Creditor-Debtor Conflict, and Populism - Gyözö Gyöngyösi; Emil Verner (The Journal of Finance, 2022)
We study the impact of debtor distress on support for a populist far-right political party during a financial crisis. Our empirical approach exploits variation in exposure to foreign currency household loans during a currency crisis in Hungary. Foreign currency debt exposure leads to a large, persistent increase in support for the populist far right. We document that the far right advocated for foreign currency debtors' interests by proposing aggressive debt relief and was rewarded with support from these voters. Our findings are consistent with theories emphasizing that conflict between creditors and debtors can shape political outcomes after financial~crises.
Keywords: 330